1998
DOI: 10.1128/jb.180.6.1525-1532.1998
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Escherichia coli rRNA Transcription by FIS during a Growth Cycle

Abstract: rRNA transcription in Escherichia coli is activated by the FIS protein, which binds upstream of rrnp 1promoters and interacts directly with RNA polymerase. Analysis of the contribution of FIS to rrn transcription under changing physiological conditions is complicated by several factors: the wide variation in cellular FIS concentrations with growth conditions, the contributions of several other regulatory systems to rRNA synthesis, and the pleiotropy of fis mutations. In this report, we show b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…In contrast to B. subtilis, none of the E. coli mutants exhibited increased biomass productivity on its preferred substrate glucose, with the sole possible exception of Fis ( Figure 7A), whose deletion leads to an increase in stable rRNA synthesis (Appleman et al, 1998). On galactose, however, the previously identified mutants with higher galactose uptakes ( Figure 5A) clearly exhibited significantly increased biomass productivity, in particular Cra, IHF A, IHF B and NagC (Figure 7B), further supporting the conclusion that E. coli actively represses its galactose uptake rate at the expense of otherwise possible rapid growth.…”
Section: Uptake Of Galactose Is Repressed In the Wild Typementioning
confidence: 96%
“…In contrast to B. subtilis, none of the E. coli mutants exhibited increased biomass productivity on its preferred substrate glucose, with the sole possible exception of Fis ( Figure 7A), whose deletion leads to an increase in stable rRNA synthesis (Appleman et al, 1998). On galactose, however, the previously identified mutants with higher galactose uptakes ( Figure 5A) clearly exhibited significantly increased biomass productivity, in particular Cra, IHF A, IHF B and NagC (Figure 7B), further supporting the conclusion that E. coli actively represses its galactose uptake rate at the expense of otherwise possible rapid growth.…”
Section: Uptake Of Galactose Is Repressed In the Wild Typementioning
confidence: 96%
“…Furthermore, SPI1 gene expression continues to depend on Fis even in late exponential phase with aeration (Kelly et al, 2004). This represents a point in the growth curve where Fis is poorly detected in E. coli (Ball et al, 1992;Appleman et al, 1998;Keane and Dorman, 2003), although approximately 10 000 Fis dimers were found to be present in an LT2 culture grown under aerated conditions to late logarithmic stage (Osuna et al, 1995). We hypothesized that the induction of SPI1 genes under non-aerated conditions could be due to the presence of the Fis protein.…”
Section: Invasion Of Epithelial Cells and Fis Expression During Growtmentioning
confidence: 99%
“…To test this hypothesis we used two approaches. First, we carried out multiple cycles of dilution of cells in fresh medium -a procedure that supports a continuous expression of fis, such that high levels of FIS protein persist in the cell (Appleman et al, 1998). Using quantitative Western analysis, we found that the repeated cycles of dilution increased the difference in the amount of GyrA and GyrB proteins (to roughly threefold for both GyrA and GyrB after four to six dilution cycles versus 1.6-fold for GyrA and 1.77-fold for GyrB in a simple shift-up experiment) between the wild-type and fis cells (Fig.…”
Section: Influence Of the Reinforcement Of Fis Expression On The Intrmentioning
confidence: 99%